2015
DOI: 10.4236/ojim.2015.52002
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Stroke: A Case Report and Review of Current Literature

Abstract: Fibromuscular dysplasia (FMD) is a non-atherosclerotic, non-inflammatory vascular disease. FMD once considered rare, is increasingly a condition recognised as an incidental finding. It is an important cause of stroke especially in younger, female patients and therefore a high index of suspicion is required. FMD has distinct pathological findings along with some pathognomonic angiographic findings ("string of beads" appearance). The mainstay of cerebrovascular FMD treatment is antiplatelet therapy but intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…8 Of the three types of FMD (intimal, medial, and adventitial), medial is the most common representing approximately 90% of fibromuscular disease. 5,[9][10][11][12] The medial type of FMD is associated with the diagnostic "string-of-beads" sign noted by imaging techniques. 6,11,[13][14][15] Cerebral aneurysms appear to be more prevalent in patients with FMD, as are aneurysms of mostly any medium-sized artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Of the three types of FMD (intimal, medial, and adventitial), medial is the most common representing approximately 90% of fibromuscular disease. 5,[9][10][11][12] The medial type of FMD is associated with the diagnostic "string-of-beads" sign noted by imaging techniques. 6,11,[13][14][15] Cerebral aneurysms appear to be more prevalent in patients with FMD, as are aneurysms of mostly any medium-sized artery.…”
Section: Discussionmentioning
confidence: 99%
“…6 A large autopsy study found the prevalence of carotid FMD to be 0.02% (4 of 20 244 autopsies). 5,[9][10][11][12] The medial type of FMD is associated with the diagnostic "string-of-beads" sign noted by imaging techniques. 3 Tobacco abuse seems to be associated with FMD to some extent.…”
Section: Introductionmentioning
confidence: 99%